PENERAPAN METODE TOPSIS UNTUK PENENTUAN PRIORITAS PERENCANAAN PROGRAM SEKOLAH - Amelia Saputri; Muhammad Nur Ikhsanto (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Education management’s a process that combines parts that are inherently unconnected to one another in order to produce a system that functions flawlessly to achieve education goals. A decision support approach is required to ensure the efficient and successful operation of the process of defining school program priorities. One of these approaches is the report card book from the education unit, used as a guideline for determining school program priorities. The suggested way for decision support using the TOPSIS method is demonstrated by the problems above.